Spatio‐temporal probabilistic query generation model and sink attributes for energy‐efficient wireless sensor networks. Issue 6 (1st November 2016) - Kumar, Pramod; Chaturvedi, Ashvini
Abstract : Proliferation in Micro‐Electro‐Mechanical‐Systems (MEMS) technology along with advancement in distributed computing infrastructure has facilitated the versatile usage and deployment of wireless sensors networks (WSNs) in last one and half decades. WSNs support large number of applications from the civilian and military regimes. Irrespective of these regimes; owing to difficulty associated with battery replenishment, proper energy usage has been at centre stage in WSNs operations. The lifetime of WSNs typically depends upon sensor's energy dissipation pattern, which is non‐homogeneous with respect to spatial distribution over any short epochs. The genesis behind this non‐homogeneity is random generation of queries, which owes to application specific spatio‐temporal parameters. Importance of spatio‐temporal parameters is ubiquitous in WSNs paradigm and uncertainties are inevitable with these parameters, although the degree of uncertainties varies in accordance to applications served. Thus, from network design perspectives, precision involved with spatio‐temporal aspects must be given due priority to obtain a mathematical model that maintains a good rapport with realistic query generation process. With these motivations, the study explores: (i) uses of energy‐efficient clustering schemes, (ii) incorporation of spatio‐temporal parameters uncertainties into probabilistic model of query generation using fuzzy‐intervals bound, and (iii) sink attributes to enhance network lifetime. For various network surveillance scenarios; the performance measures average residual energy status and service‐time‐duration are estimated and analysed.